Cars toon. Mater's tall tales [videorecording (DVD)] - Ferguson, Keith, 1972-; Larry, the Cable Guy; Lasseter, John; Gibbs, Rob; Rae, Kori; Mothersbaugh, Mark; Coon, Bruno (Disney DVD., 2010)
Join Mater, the heart and soul of Radiator Springs, and all your favorite characters from the world of Cars as they take you on a fun-filled ride that will have your family roaring with laughter. Includes Rescue squad Mater, Tokyo Mater, Heavy metal Mater, El Materdor, and others.